A New Copy of the 1522 Psalter by Francysk Skaryna - Shutova, Olga (Slavistica Vilnensis, 2025)
This announcement reports the discovery of a new copy of the Psalter published by Francysk Skaryna in 1522 (presumably a part of the Small Travel Book printed in Vilnius). The copy, held at the Herzogin Anna Amalia Bibliothek in Weimar (Germany), has until now remained unknown to researchers. A preliminary bibliographic description of the copy is provided, and prospects for further research are outlined.